Assessing the Characteristic of Bands Combination in Log Ratio Change Detection Using SAR Imagery - Hartanto, Agus Dwi; Setyawan, Dwi; Taqwa, Ferdinand Hukama (Program Pascasarjana Universitas Sriwijaya, 2025)
Log ratio is one of the change detection techniques often used in SAR image-based flood inundation analysis where the differences in characteristics between its polarizations are expected to complement each other and provide optimal predictions. This research aimed to identify the characteristics of the output generated from various potential combinations utilizing log ratio change detection. The study utilized Sentinel-1 GRD IW dual polarization mode before and during the flood event as its main datasource. Briefly, the data processing consists of preprocessing, collocation, and change detection, which were subsequently followed by analysis and evaluation. The analysis results indicated a highly significant difference in characteristics among the four outputs of log ratio change, where the combinations of VH1/VH2 and VV1/VV2 detected much smaller changes compared to the combinations of VV1/VH2 and VH1/VV2. The VV1/VH2 combination acts as a counterpoint to the VH1/VV2 combination, as the changes identified in VV1/VH2 showed a tendency towards positive values, whereas the opposite is true for VH1/VV2. The evaluation results show that the highest frequency of errors in detecting changes sequentially was observed in the combinations of VH1/VV2, VV1/VH2, VV1/VV2, and VH1/VH2.